(untitled) (International Journal of Environmental Sciences, 2025)
Relevance: Breast cancer ranks among the foremost causes of cancer-related mortality in women globally. Cyclin D1, an essential regulator of the cell cycle, has been associated with carcinogenesis and the advancement of breast cancer. The study aimed to investigate the correlation between Cyclin D1 immunohistochemistry expression and histopathological characteristics in breast cancer patients, emphasizing age, tumor grade, histological type, and HER2 status. Methodology: This study was conducted on a sample of 40 cases of breast cancer diagnosed in women from Najaf Governorate. This cross-sectional analytical investigation investigated the immunohistochemistry expression of Cyclin D1 in breast cancer tissues. Forty samples were obtained from Al-Sadr Teaching Hospital and private laboratories in Najaf (Iraq) from July 2024 to May 2025. Expression levels were assessed via immunohistochemistry and associated with clinicopathological characteristics. Results: Cyclin D1 expression was positive in 72.5% of cases, with the highest expression noted in patients aged 50–59 years, homemakers, and individuals diagnosed with invasive ductal carcinoma and grade II malignancies. HER2-negative cancers exhibited an increased prevalence of Cyclin D1 expression. Significant correlations were identified between Cyclin D1 expression and age, tumor grade, histological type, and HER2 status (P≤0.05). Finally, Cyclin D1 shows potential as a key biomarker for predicting breast cancer, highlighting its clinical importance in detection, classification, and treatment choice.